Plato and Plotinus in front of the problem of separation - Fattal, Michel (Revista Archai, 2021)
The current study seeks (a) to analyze in a precise manner the philosophical and doctrinal reasons that led Plato and Plotinus to want to solve the problem of separation and (b) to appreciate the originality and relevance of the solution to this problem developed by Plato and his Neoplatonic interpreter.